Diversity of Enforcement Titles in Cross-border Debt Collection in the EU: National Report: Cyprus - Christofi, Despina; Loizou, Demetra (2022)
Applying a systematic approach, this report addressess the main features of enfrocement titles in Cyprus. It focuses on judgments, court settlements and notarial deeds, scrutinizing their content, form and effects. It conveys theoretical insight into the subject matter as well as conclusions from relevant case law.
Keywords: enforcement title; cross-border enforcement; EU law; civil procedure law; cyprus